On Positive Solution of a New Class of Nonlocal Fractional Equation with Integral Boundary Conditions - Noora Housain (Al-Rafidain Journal of Computer Sciences and Mathematics)
We prove that a positiveasolution to a given boundaryaproblem exists and is unique. This new boundaryacondition  relates theanon-local unknown value of unknownafunction at λ with its influenceadue to aasup-strip (µ,1), 0<λ<µ<1 .Our resultsaare aobtainted by using " Banach andaKrasnoselskii’satheorems"a linked to anywhere. Some classicalatheorems of fixedapoints assistance to achieve the greatestaresults.